Local Knowledge of Disaster Mitigation in The Traditional Umeak An House of Rejang Tribe in Bengkulu - Soni, Aprianto; Yunita, Mirna; Alfi, Muhammad; Sihaini, Etika; Utami, Anggun Dwi (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2026)
Bengkulu Province is situated within a high-risk zone necessitated by plate subduction activity and the permanent presence of the Semangko Fault. Amidst such persistent seismic threats, the local population exhibits a tendency to transition toward rigid concrete structures which are susceptible to collapse while simultaneously abandoning resilient traditional architecture. This qualitative study employs a descriptive analytical method to examine the local wisdom of disaster mitigation embodied in the traditional dwellings of the Rejang Tribe known as Umeak An as a model for adaptive housing. The research was conducted in North Bengkulu Regency specifically within the Arga Makmur and Arma Jaya Districts. Primary data were gathered through direct technical observations and in-depth interviews with four key informants comprising two community leaders one tribal elder of the Rejang community and a tribal chief. The information was processed using comparative descriptive techniques oriented toward value discovery to synchronize empirical realities with modern engineering parameters. Findings demonstrate that Umeak An possesses engineering superiority through its non-nailed joint system or papurus and an elastic stilt structure that functions as a dynamic damper. This study concludes the imperative of integrating vernacular elasticity principles into modern construction regulations to achieve sustainable residential resilience.